Experimental Study Of Ready Mix Wastewater Utilization For New Concrete Mixtures - Agung Sumarno; Aditya Hendric Nur Prasetyo (Journal of World Conference (JWC), 2021)
The use of waste water that is still in accordance with the standards of SNI 06-6989 and APHA 3120B can be reused as a concrete mixture material in the concrete production process at the Batching Plant, especially for low- quality concrete. The purpose of this study was to determine the effect of the use of wastewater with variations of 0%, 25%, 50%, 75% and 100% on the quality or quality of concrete. Based on the results of the study, it was found that at the beginning of the concrete pavement period, the chemical content contained in wastewater from the concrete production process will interfere with the hydration process so that the compressive strength of concrete at the age of 7 days tends to decrease. However, after the age of 28 days, the dissolved solids in the wastewater from the concrete production process fill the pores in the concrete so that the compressive strength of the resulting concrete becomes higher. The value of the use of wastewater to the optimal composition of the concrete mix design is 75% of the total volume of water required. This is based on the results of the compressive strength test which reached 93.37% of normal concrete at the age of 7 days, 100.59% of normal concrete at the age of 14 days and 105.94% at the age of 28 days with the slump and flow table test results of 16cm and 38cm.